2004
DOI: 10.1007/s00424-004-1348-4
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Nav1.5 by ?1- and ?3-subunit co-expression in mammalian cells

Abstract: Cardiac sodium channels (Na(v)1.5) comprise a pore-forming alpha-subunit and auxiliary beta-subunits that modulate channel function. In the heart, beta1 is expressed throughout the atria and ventricles, whilst beta3 is present only in the ventricles and Purkinje fibers. In view of this expression pattern, we determined the effects of beta3 and beta1 co-expression alone, and in combination, on Na(v)1.5 stably expressed in Chinese hamster ovary cells. The current/voltage relationship was shifted -5 mV with eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
54
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 46 publications
9
54
0
Order By: Relevance
“…They showed that the lack of Na V β3 induced a ≈30% decrease in cardiac Na + peak current amplitude associated with a shift of the steadystate inactivation curve toward negative potentials while other I Na biophysical parameters were not altered, thus confirming previous studies in mammalian heterologous expression system (Ko et al, 2005). As a consequence, Scn3b ] mice exhibited decreased ventricular conduction, shortened ventricular action potential duration, and refractory period and increased incidence of arrhythmias under programmed electrical stimulation in ex vivo Langendorffperfused hearts (Hakim et al, 2008).…”
Section: Scn3b Knockout Mousesupporting
confidence: 77%
“…They showed that the lack of Na V β3 induced a ≈30% decrease in cardiac Na + peak current amplitude associated with a shift of the steadystate inactivation curve toward negative potentials while other I Na biophysical parameters were not altered, thus confirming previous studies in mammalian heterologous expression system (Ko et al, 2005). As a consequence, Scn3b ] mice exhibited decreased ventricular conduction, shortened ventricular action potential duration, and refractory period and increased incidence of arrhythmias under programmed electrical stimulation in ex vivo Langendorffperfused hearts (Hakim et al, 2008).…”
Section: Scn3b Knockout Mousesupporting
confidence: 77%
“…Conductance as a function of voltage was derived from the current–voltage relationship and fitted by a Boltzmann function as described previously 24. Decays of macroscopic currents were fitted to a single exponential function and time constants were determined 25. For steady‐state inactivation, neurons were held at −120 mV and test potentials from −115 mV to −10 mV for 1 sec at 5 mV increments were applied.…”
Section: Methodsmentioning
confidence: 99%
“…Some groups have reported that β1 increases Na V 1.5 currents with or without affecting voltage dependence or channel kinetics, while others have reported no effect of β1 on Na V 1.5 current (20,(33)(34)(35)(36)(37). The β1B variant has to date only been studied in coexpression studies with the neuronal sodium channel Na V 1.2 (encoded by SCN2A), where it was shown to increase sodium current and cause a small negative shift in voltage dependence of activation (19).…”
Section: Figurementioning
confidence: 99%